Peran Kualitas Audit dalam Memediasi Pengaruh Teknologi dan Independensi Terhadap Efektivitas Audit: Studi pada BPKP Kalimantan Barat - Yulika; Rahma Maulidia; Muhsin (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This Audit effectiveness is an important aspect of state financial supervision, especially in the midst of demands for public accountability and technological advances. This study examines the effect of technology and independence on audit effectiveness, with audit quality as a mediating variable at the BPKP Representative of West Kalimantan. This research is based on agency theory which highlights the relationship between principals and agents in accountability and reporting. The research method is quantitative, with data obtained from 46 auditors through questionnaires. The data were analyzed using the Partial Least Square (PLS) approach. The results of the analysis indicated that auditor independence significantly contributed to audit effectiveness, while the direct effect of technology was not statistically proven. However, technology and independence were shown to significantly contribute to improving audit quality. Audit quality acts as a mediator that connects the effect of technology and independence on audit effectiveness. This finding indicates that although technology has no direct impact, its contribution is important through improving audit quality. This research confirms the importance of strengthening audit quality as a key factor in improving audit effectiveness, especially in the face of technological developments and maintaining auditor independence in the public sector.